2019
DOI: 10.1002/jcb.29455
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone HspB2 inhibited pancreatic cancer cell proliferation via activating p53 downstream gene RPRM, BAI1, and TSAP6

Abstract: Heat shock proteins (HSPs) were known as the molecular chaperones, which play a pivotal role in the protein quality control system, ensuring correct folding of proteins, and facilitating the correct refolding of damaged proteins via the transient interaction with their substrate proteins. They also practice in the regulation of cell cycles and are involved in apoptosis. We found that HspB2 was almost completely silent in pancreatic cancer and few studies investigated the role of HspB2 in cancer cells, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Machlenkin et al reported that STEAP3 was highly expressed in prostate cancer [13]. Subsequently, increased expression of STEAP3 was proved in a variety of tumor tissues, including breast cancer [42][43][44][45][46][47]. The activation of p53 is induced by a variety of stress signals, including DNA damage, oxidative stress, and activated oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Machlenkin et al reported that STEAP3 was highly expressed in prostate cancer [13]. Subsequently, increased expression of STEAP3 was proved in a variety of tumor tissues, including breast cancer [42][43][44][45][46][47]. The activation of p53 is induced by a variety of stress signals, including DNA damage, oxidative stress, and activated oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HSPs have been reported to be involved in cancer cell proliferation, survival, and apoptosis [45][46][47]. Studies have shown that expression of HSPB2 is reduced in esophageal squamous cell carcinoma [22] and pancreatic cancer, which can inhibit the progression of pancreatic cancer [48]. HSPB2 also inhibits the apoptotic pathway by inhibiting the activation of caspases-8 in breast cancer [49].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB2 also inhibits the apoptotic pathway by inhibiting the activation of caspases-8 in breast cancer [49]. Moreover, studies have revealed that HSPB2 is a novel target of p53 [50], which can restore the transcriptional activity of mutant p53 and inhibit tumor progression to a certain extent [48]. However, there have been no reports to date concerning the effect of HSPB2 on CRC as a downstream of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HSPs have been reported to be involved in cancer cell proliferation, survival, and apoptosis [45][46][47]. Studies have shown that expression of HSPB2 is reduced in esophageal squamous cell carcinoma [22] and pancreatic cancer, which can inhibit the progression of pancreatic cancer [48]. HSPB2 also inhibits the apoptotic pathway by inhibiting the activation of caspases-8 in breast cancer [49].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB2 also inhibits the apoptotic pathway by inhibiting the activation of caspases-8 in breast cancer [49]. Moreover, studies have revealed that HSPB2 is a novel target of p53 [50], which can restore the transcriptional activity of mutant p53 and inhibit tumor progression to a certain extent [48]. However, there have been no reports to date concerning the effect of HSPB2 on CRC as a downstream of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%